Analisis Peran Kepala Sekolah Dalam Upaya Meningkatkan Mutu Manajemen Sekolah Di SD Negeri Sukamenak 06 Kabupaten Bandung - Arfan, Arfan; Qomario, Qomario; Soraya , Rahayu (Gayaku Publisher, 2024)
This study aims to analyze the role of school principals in efforts to improve the quality of school management. The role of the school principal is a critical factor in achieving quality education goals. This research is a descriptive qualitative research with the type of research design is a case study, data collection is done through observation, interviews, and documentation. Respondents to this study were school principals and teaching staff at Sukamenak 08 Public Elementary School, Bandung Regency. The results of the study show that school principals have an important role in improving the quality of school management, principals play the role of leaders, decision makers, communicators, supervisors, and staff developers. Through his leadership the principal provides direction and motivation to the teaching staff to improve the quality of teaching. In addition, the principal also supervises the learning process and provides guidance to teachers who need it. This research also identified some limitations. First, this research was conducted in a limited number of schools, so generalization of research findings needs to be done with caution. Second, this research is limited to data obtained from observation, interviews, and document analysis, so there is a possibility of bias in the interpretation of the data.